2020
DOI: 10.1038/s41598-020-68809-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ventilation use and occupant behaviour on surface microorganisms in contemporary social housing

Abstract: Homes satisfy our most basic needs for shelter and should be designed to provide a comfortable and safe environment. However, provision of housing is constrained through cost and legislation encompassing appearance, structure, materials, provision of services and energy performance. Most of the time these align to human needs, but there are conflicts, particularly with respect to energy and ventilation and their influence on health. In a bid to reduce energy and carbon emissions, the building sector is deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…The built environment designs affect not only the human microbiome, health, and behavior but also affect other associated macroorganisms like pets. So, human health can be made better by modifying the indoor microbiome through architectural design [35,50,52]. Efforts are going on to design selective pressures and use microbial resources to create a healthy symbiotic built microbiome [53].…”
Section: Environmental Factors: Indoor and Outdoormentioning
confidence: 99%
See 1 more Smart Citation
“…The built environment designs affect not only the human microbiome, health, and behavior but also affect other associated macroorganisms like pets. So, human health can be made better by modifying the indoor microbiome through architectural design [35,50,52]. Efforts are going on to design selective pressures and use microbial resources to create a healthy symbiotic built microbiome [53].…”
Section: Environmental Factors: Indoor and Outdoormentioning
confidence: 99%
“…Incorporation of well‐ventilated spaces into architectural designs has long been known to influence human health, wellbeing, and productivity [52]. Ongoing research tries to decode the influence of specific ventilation design on indoor microbial community structure and diversity.…”
Section: Environmental Factors: Indoor and Outdoormentioning
confidence: 99%
“…The effects on health are different. When high counts of environmental bacteria, such as Staphylococcus epidermidis , Micrococcus and Flavobacterium, are found scattered on skin flakes, these can be considered indicators of inadequate ventilation [ 4 ]. Researchers have suggested that gram-negative bacteria, such as Pseudomonas aeruginosa , or other bacteria such as thermophilic actinomycetes, Streptomyces albus , Bacillus subtilis and complex communities of microorganisms in biofilms are aetiological agents of hypersensitivity pulmonary disease [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces in various rooms in the homes of older adults were sampled by Sharpe et al 15 . The samples were then examined using microbiological culture methods.…”
mentioning
confidence: 99%